In vitro evaluation of microleakage under a glass ionomer surface protector cement after different enamel treatment procedures - (:unkn) unknown (My University, 2012)
AIM: The aim of this in vitrostudy was to evaluate the microleakage of a glass-ionomer surface-protector cement (GC Fuji Triage) placed onto the fissure surfaces of extracted human molars prepared using six different treatment procedures. METHODS: Ninety-six extracted non-carious human molar teeth were divided into five enamel treatment groups: (Gp1) air-abraded (Micadent II, Medidenta); (Gp2) air-abraded and conditioned with 10% polyacrylic acid (GC dentin conditioner); (Gp3) prepared by a bur designed for enameloplasty (#8833 Komet); (Gp4) prepared with a bur and conditioned; (Gp5) conditioned; and (Gp6) no treatment (control). The teeth were then sealed with GC Fuji Triage. The teeth were thermocycled and left in distilled water or artificial saliva for one week, coated twice with nail varnish, and stained in a dye. They were sectioned and scored for microleakage. RESULTS: All groups showed microleakage. Samples that were kept in saliva had better results than those that were kept in distilled water (P<0.05). Samples conditioned before the treatment were also better than non-conditioned groups (P<0.05). In distilled water and artificial saliva, the range of the groups was, from the best, Gp2<Gp4<Gp5=Gp3<Gp1=Gp6 and Gp4<Gp2<Gp3<Gp5<Gp1<Gp6, respectively. CONCLUSIONS: This in vitrostudy showed that the microleakage under the GIC material could be improved after treatment procedures such as conditioning, and/or air abrasion, and/or ameloplasty.
Keywords: Humans; Surface Properties; Molar; Dental Leakage; Glass Ionomer Cements; Pit and Fissure Sealants; Dental Enamel; Dental Etching